2016
DOI: 10.1097/md.0000000000003715
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling Components

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…[28,29] Furthermore, our literature search and review showed that DLL3 expression was not associated with any survival significance of patients with small-cell lung cancer but that elevated DLL3 expression was associated with poor overall survival of patients with lung adenocarcinoma, but not of patients with lung squamous cell carcinoma and with poor overall survival of patients with nonsmall-cell lung cancer. [39,44,45] Thus, our present data on the association of DLL3 overexpression with reduced overall survival of patients with endometrial cancer are consistent with that of the lung adenocarcinoma study.…”
Section: Discussionsupporting
confidence: 89%
“…[28,29] Furthermore, our literature search and review showed that DLL3 expression was not associated with any survival significance of patients with small-cell lung cancer but that elevated DLL3 expression was associated with poor overall survival of patients with lung adenocarcinoma, but not of patients with lung squamous cell carcinoma and with poor overall survival of patients with nonsmall-cell lung cancer. [39,44,45] Thus, our present data on the association of DLL3 overexpression with reduced overall survival of patients with endometrial cancer are consistent with that of the lung adenocarcinoma study.…”
Section: Discussionsupporting
confidence: 89%
“… 19 The database was used as previously described. 20 Briefly, the genes were entered into the database of GC to obtain Kaplan–Meier survival plots. The Multivariate Cox regression model was used and HR, 95% CI, and log-rank p -value were calculated and displayed.…”
Section: Methodsmentioning
confidence: 99%
“…25 High DLL3 expression predicts poor overall survival (OS) in lung adenocarcinoma, playing an opposing prognostic role to DLL1. 26 In high-grade neuroendocrine lung tumors (including small cell lung cancer (SCLC) and large-cell neuroendocrine cancer (LCNEC)), DLL3 is overactive at the tumor cell surface and positively correlates with achaete-scute homolog-1 (ASCL1), a member of the BHLH family of transcription factors that is involved in neuroendocrine cell fate decisions. [27][28][29] ASCL1 activates DLL3 by binding to special E-box sites in the DLL3 promoter, as observed in the dorsal neural tube.…”
Section: Delta-like Ligands In Lung Cancermentioning
confidence: 99%